ANALISIS INOVASI MELALUI KEMAJUAN TEKNOLOGI PADA PRODUKSI DAN PEMASARAN BATIK DI KECAMATAN DANAU TELUK KOTA JAMBI - Sulaiman, Sulaiman; Nengsih, Titin Agustin; Agusriandi, Agusriandi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
Technological advances have had a great impact on the development of production and product marketing innovation. The purpose of this study is to analyze how much technological advances have had an impact on product production and marketing innovation in 4 batik entrepreneurs, Danau Teluk District, Jambi City. The research method used is descriptive research with a qualitative approach. Data was collected through observations and interviews with batik producers, batik traders and visitors to the batik market in Danau Teluk District of Jambi City. The results showed that technological advances have had a major impact on the innovation of production and marketing of the products of 4 batik entrepreneurs in Danau Teluk District, Jambi City. Production innovation through the use of technological advances opens up new opportunities for batik makers to quickly create various motifs, designs and be more efficient and effective. Meanwhile, marketing innovations through the use of the internet and social media have allowed batik entrepreneurs to reach a wider market, making it easier for consumers to shop online. Technological innovation has had a positive impact, but efforts are still needed to develop innovation through technological advances in the production and marketing of products of 4 batik entrepreneurs in Lake Teluk District, Jambi City, the development of innovation through technological advances in the production and marketing of batik products constrained by the strength of capital, human resources and knowledge of technological advances.